If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7y + -42 = 0 Reorder the terms: -42 + 4x + 7y = 0 Solving -42 + 4x + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 4x + 42 + 7y = 0 + 42 Reorder the terms: -42 + 42 + 4x + 7y = 0 + 42 Combine like terms: -42 + 42 = 0 0 + 4x + 7y = 0 + 42 4x + 7y = 0 + 42 Combine like terms: 0 + 42 = 42 4x + 7y = 42 Add '-7y' to each side of the equation. 4x + 7y + -7y = 42 + -7y Combine like terms: 7y + -7y = 0 4x + 0 = 42 + -7y 4x = 42 + -7y Divide each side by '4'. x = 10.5 + -1.75y Simplifying x = 10.5 + -1.75y
| 37.25+0.50x=100 | | 12-18x= | | 35.7+0.50x=100 | | 2v-10v=6(2v+4)-12(2+5v) | | -88+14=21 | | 3(x-1)=2x+x+2 | | 6(-1+2m)=-90 | | x-(x*0.07)=42627 | | -5x-7(4-3x)=-156 | | x-(x*0.07)=39643 | | 89=6(x-7)+5 | | (5y+10)=60 | | -4y+8-3x+4y+9+5x= | | x/2(1-x) | | x-(x*0.07)=36868 | | 4x-70= | | 3n-4(3n-7)=100 | | 8d-4e=11d+3e | | 82=-8(x-3)-6 | | D/5=11 | | 6x-12=4x-18 | | -2(x+2)=2x+3+1 | | 6x+2=8x-20 | | x-(x*0.07)=34287 | | 3x^4+17x^2+20=0 | | 3m+8x= | | 6y+12z= | | 15x-3(3z+4)=6 | | 16=13-3x | | -8k+9=-15 | | 6(7x+1)=300 | | 180=4x-70 |